The Perspectives Of Four Muslim Scholars On Islamisation Of Science - Abu Hassan, Mahadi; Sidek, Safiah; Mohamed, Shahrulanuar; Kudus, Norliah (Publications International, 2016)
Islamization of science has become a debatable issue among Muslim scholars since 1970's. This debate emerged due to the crisis of modern Western science that views a dichotomy between science and religion. To date, there have been many prominent Muslim scholars from the West and the East who discuss this dichotomy based on their understanding and expertise. This paper aims to report a study that analyzes the discourse of Islamization of knowledge from the perspective of four Malaysian Muslim scholars, namely Syed Muhammad Naquib al-Attas, Osman Bakar, Shaharir Mohamad Zain and Wan Mohd Nor Wan Daud. The selection of scholars are in line with their scholarship and contribution to the discourse of science both nationally and internationally. Based on interviews and analysis of documents written by the four scholars, four terminologies that structure the discourse of Islamization of knowledge have been identified. The four terminologies the paradigm of Tawheed, indigenization of science and technology, philosophy of Islam and issues of securalism. It is found that that the core philosophy and responses of these scholars in Islamization of science are very relevant in all domains of knowledge. The paper also highlights that their contributions to the discourse of Islamization of science have significant impact not only in Malaysia, but also in a variety of disciplines across the Muslim world.